Akar Historis dan Perkembangan Islam di Inggris - Budi, Syah (Tasamuh: Jurnal Studi Islam, 2018)
This paper will reveal the historical roots and Islamic development in British. The discussion covers various areas of study pertaining to historical situations. The study tends to focus on the search for the historical roots of Islam in the 7th to 15th and 16th-17th centuries, and also the development of Islamic institutions in British contemporer.The historical roots of Islam in Britain have existed since the discovery of several coins with the words 'laa ilaaha illallah' belonging to the King of Central England, Offa of Mercia, who died in 796. The history records that this Anglo Saxon King had trade ties with the peoples Muslim Spain, France and North Africa. In addition, also found in the 9th century the words 'bismillah' by Kufi Arabic on Ballycottin Cross. Indeed, in the eighth century history has noted that trade between Britain and the Muslim nations has been established. In fact, in 817 Muhammad bin Musa al-Khawarizmi wrote the book Shurat al-Ardhi (World Map) which contains a picture of a number of places in England. In the 12th century, when the feud with Pope Innocent III, King John established a relationship with Muslim rulers in North Africa. Later, in the era of Henry II, Adelard of Bath, a private teacher of the King of England who had visited Syria and Muslim Spain, translated a number of books by Arab Muslim writers into Latin. The same is done by Danel of Marley and Michael Scouts who translated Aristotle's works from Arabic. In 1386 Chaucer wrote in his book prologue Canterbury of Tales, a book that says that on the way back to Canterbury from the holy land, Palestine, a number of pilgrims visit physicists and other experts such as al-Razi, Ibn Sina and Ibnu Rusyd. At that time Ibn Sina's work, al-Qanun fi al-Tibb, had become the standard text for medical students until the seventeenth century.The development of Islam increasingly rapidly era after. In 1636 opened the Arabic language department at the University of Oxford. In addition, it is well known that the English King Charles I had collected Arabic and Persian manuscripts. In the era of Cromwell's post civil war, the Koran for the first time in 1649 was translated in English by Alexander Ross. In the nineteenth century more and more small Muslim communities, both immigrants from Africa and Asia, settled in port cities such as Cardif, South Shield (near New Castle), London and Liverpool. In the next stage, to this day, Islam in Britain has formally developed rapidly through the roles of institutions and priests, and the existence of Islam is also widely acknowledged by the kingdom, government, intellectuals, and the public at large